Parameter Genetik Padi Sawah Dataran Tinggi - Zen, Syahrul (Jurnal Penelitian Pertanian Terapan, 2012)
The experiment using 14 gonotipe exercised on agroekosistem the high lands rice of with elevation 850 to 1050 m asl on five environment in West Sumatra. Aranged in a randomized complete block design, with three replication. Variable measured were agronomic characters, yield componen on yield. The result showed that in general all the characters observed it has value expect heritability high , and value genetic gain, as well as a coefficient the genetic variation in general also massive exc weights 1 000 grains with value expect both the parameters low. Based on the value of a parameter this genetic and to increase efiesien selection and activities selection be done in the early . Keywords; high land rice, heritability, koefisien variance genetic.